Lightning as a major driver of recent large fire years in North American boreal forests - Veraverbeke, Sander; Rogers, Brendan M.; Goulden, Mike L.; Jandt, Randi R.; Miller, Charles E.; Wiggins, Elizabeth B.; Randerson, James T. (Nature climate change, 2017)
Changes in climate and fire regimes are transforming the boreal forest, the world’s largest biome. Boreal North America recently experienced two years with large burned area: 2014 in the Northwest Territories and 2015 in Alaska. Here we use climate, lightning, fire and vegetation data sets to assess the mechanisms contributing to large fire years. We find that lightning ignitions have increased since 1975, and that the 2014 and 2015 events coincided with a record number of lightning ignitions and exceptionally high levels of burning near the northern treeline. Lightning ignition explained more than 55% of the interannual variability in burned area, and was correlated with temperature and precipitation, which are projected to increase by mid-century. The analysis shows that lightning drives interannual and long-term ignition and burned area dynamics in boreal North America, and implies future ignition increases may increase carbon loss while accelerating the northward expansion of boreal forest. The boreal forest is being transformed by changes in its climate–fire regime. Analysis now shows that lightning drives year-to-year and long-term ignition and burned area trends in boreal North America.